Monetary policy, asset prices and financial institutions. (1st November 2013) - Booth, Philip
Abstract The operation of monetary policy is likely to affect securities markets and asset values. This is of relevance to actuaries who work in or advise non-bank financial institutions such as pension funds and insurance companies. This paper examines different theories of monetary policy and the relationship between monetary policy and asset prices. It is found that central bank models have, at least until recently, tended to sideline consideration of the transmission of monetary policy through asset markets but that, with the implementation of quantitative easing, it is a subject that cannot be ignored. Many monetary schools, in fact, suggest that asset markets can be significantly affected by changes to monetary policy and those schools have lessons for important aspects of actuarial theory and practice.